SYNONYMS, ANTONYMS, HOMONYMS IN ENGLISH - Xaitkulova Arjuman, (TADQIQOTLAR, 2026)
Abstract   The  English  language  contains  a  wide  range  of  lexical  relationships  that contribute  to  its  richness  and  flexibility.  Among  these,  synonyms,  antonyms,  and homonyms  are  fundamental  in  understanding  how  meaning  is  constructed  and interpreted. This article provides a detailed analysis of these three categories, including their definitions, types, functions, and roles in communication. By examining their semantic  and  practical  significance,  the  article  highlights  how  mastery  of  these relationships  enhances  vocabulary  acquisition,  linguistic  competence,  and  effective communication in both spoken and written English.